Jake and the spyglass - La Rose, Melinda; Character Building Studio; The Disney Storybook Art Team (New York : Disney Press, 2014)
When Captain Hook loses his spyglass he steals Jake's, and Jake and his crew try to get it back.
Primary
Keywords: Never-Never Land (Imaginary place) -- Fiction; Pirates -- Fiction